Paesani versus Paisanos: The Relative Failure of Spanish Immigrants in Buenos Aires during the Age of Mass Migration - Leticia Arroyo Abad; Noel Maurer; Blanca Sánchez-Alonso (European Historical Economics Society (EHES), 2020)
Millions of immigrants chose Argentina as the land of opportunity during the era of mass migration. Two immigrant groups, Italians and Spaniards, dominated the immigration flows. Despite higher literacy and their linguistic advantages, in Buenos Aires Spaniards fared worse when compared to Italians. By 1895, Italians enjoyed higher wages. What explains their paths in the city of Buenos Aires? We find that the Italian community capitalized upon pre-existing cultural traditions to establish denser and more effective networks to match their compatriots with economic opportunities. The more individualistic Spanish were unable to keep pace, despite their initial cultural, linguistic, and educational advantages.
Keywords: N36; F22; 330; migration; networks; Buenos Aires